Swimming fastest : the essential reference on technique, training, and program design - Maglischo, Ernest W., ....- (Champaign : Human Kinetics, 2003)
Swim faster and stronger with Swimming Fastest, the ultimate swimming guide for stroke technique and training methods for competitive swimming. By offering a thorough analysis of each of the primary strokes, this book explains the how and why of training and execution, includes sample workouts, and is the best way to trim seconds off your time.
Keywords: Zwemmen